Wybór dyrektora szkoły – wymagania i procedura konkursowa w Polsce i Ukrainie. W kierunku dobrych praktyk - Szafran, Joanna; Hrybiuk , Olena (Studia Edukacyjne, 2020)
Modern school requires modern leaders. These are adequately educated people with necessary skills and ability to perform the responsible work of the principal. These indisputable statements and criteria are not taken into account when selecting school principals; nor are they taken into consideration in the existing competition requirements and procedures for the headmaster’s position. The article discusses and analyzes the criteria, provides recommendations to improve existing requirements and procedures. Critical reflection concerns the procedure of choosing a school principal within the framework of the current legal regulation in Poland and Ukraine. Special attention is paid to the requirements and procedures, including the qualification, psychological predisposition and skills of future school principals. The result of a critical analysis of existing standards and the proposal of changes are aimed at a more professional selection of managers in education.